The performance of the 3DES and Fernet encryption in securing data files - Mohd, Siti Munirah; Kamarudin, Shafinah; Yahya, Norhanizah; Hasan, Sazlinah; Mahamad Zakaria, Muhammad Luqman; Sulaiman, Sahimel Azwal; Setyohadi, Djoko Budiyanto (Little Lion Scientific, 2024)
The number of cyber attacks launched has increased five-fold since the advent of the Coronavirus Disease Pandemic (COVID-19) in 2019. Ransomware is currently one of the highest digital risks as it aids cybercriminals to use persistent threat tools and techniques to get access to targeted networks by way of third parties. Therefore, this study aims to implement the symmetric encryption algorithms known as 3DES and Fernet methods as a means for securing files. In addition, this study evaluates the 3DES and Fernet encryption methods’ performance in protecting confidential file. This study significantly contributes in comprehending Fernet and 3DES methods for securing confidential files, identifying the most efficient cryptographic symmetric algorithm for file security, and providing comparative results between Fernet and 3DES. This study applies both 3DES and Fernet in the scenario of client-server architecture in performing encryption and decryption processes. The results from the current study has shown successful implementation of these two encryption methods for both the encryption and decryption processes. In addition, this study evaluates the temporal efficiency for the encryption process. Five different text file sizes ranging from 10KB to 50KB were used for the experimental trial in evaluating the performance of both encryption methods. The outcome reveals that the Fernet encryption method performs better than 3DES. © Little Lion Scientific.